2013
DOI: 10.2460/javma.242.12.1679
|View full text |Cite
|
Sign up to set email alerts
|

Development of a survey instrument to assess health-related quality of life in small animal cancer patients treated with chemotherapy

Abstract: The QOL instrument was easy to use and enhanced client perception of patient care and clinician concern. Owners enjoyed the opportunity to complete the survey. Since questions regarding play behaviors, clinical signs of disease, and canine happiness were significant indicators of changes in QOL, these should be included in future studies. Quality of life assessment may facilitate treatment decisions and assessment of canine patients undergoing chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The veterinary surgeon and veterinary nurse should assess this and train and support caregivers in quality of life assessment. Several quality of life questionnaires for veterinary patients have been published and assessed and can be used to make objective and ongoing assessments of a patient's performance status (Wiseman-Orr and others 2004, Yazbek and Fantoni 2005, Lynch and others 2011, Crawford and others 2012, Iliopoulou and others 2013, Giuffrida and Kerrigan 2014). …”
Section: Quality Of Lifementioning
confidence: 99%
“…The veterinary surgeon and veterinary nurse should assess this and train and support caregivers in quality of life assessment. Several quality of life questionnaires for veterinary patients have been published and assessed and can be used to make objective and ongoing assessments of a patient's performance status (Wiseman-Orr and others 2004, Yazbek and Fantoni 2005, Lynch and others 2011, Crawford and others 2012, Iliopoulou and others 2013, Giuffrida and Kerrigan 2014). …”
Section: Quality Of Lifementioning
confidence: 99%
“…The World Health Organization (WHO) defines quality of life as; individual perception if their position in life in the context of the culture and value system in which they live and in relation to their goals, expectations, standards and concerns . Some studies have shown that disease severity and psychological stress affected on quality of life (Caffey et al, 1999;Farzianpour et al, 2012;Iliopoulou et al, 2013;Ovayolu et al, 2013). In other studies, quality of life has been linked to all factors of cancer disease including the type of treatment, type and severity of cancer (Bare and Smeltzer, 2004;Deng et al, 2013;Li et al, 2013;Ding et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As twothirds of canine gliomas occur in the forebrain, seizures and behavior changes are the most commonly reported clinical signs (23,28,29). In addition, healthrelated quality of life surveys for use in the assessment of clinical disability in dogs with cancer do exist, although the current iterations have not been specifically developed for or validated in dogs with brain tumors (30). The prognosis for dogs with gliomas is also poor, with death occurring weeks to months following diagnosis in the absence of treatment.…”
Section: Spontaneous Canine Gliomas As a Faithful Model Of Human Diseasementioning
confidence: 99%